Integrating Swanson’s Caring Theory into Discharge Planning Education: Effects on Patient Satisfaction in Postoperative Care - Pradini, Septi Wahyu; Putra, Kuswantoro Rusca; Kapti, Rinik Eko (Journal of Nursing Science Update (JNSU), 2025)
The patient's beliefs have been shown to influence their ability to perform self-care in a manner that minimizes post-operative complications. Patient satisfaction with the quality of discharge planning education is also a factor that can influence patient acceptance to undergo post-operative care at home. Patients who are dissatisfied with the nurses' information and instructions are likely to demonstrate noncompliance postoperatively. The integration of the Swanson Theory of Caring approach into discharge planning education has the potential to enhance patient satisfaction. The objective of this study was to analyze the effect of discharge planning education utilizing the Swanson Theory of Caring approach on increasing patient satisfaction in post-operative care. The quasi-experimental study employed a non-randomized pretest-posttest control group design. The study's participants were 78 patients, who were divided into two groups: a control group and an intervention group. The control group received discharge planning education according to standard operating procedures. The intervention group received discharge planning education with the Swanson Theory of Caring approach. The results of the Wilcoxon signed-rank test demonstrate a p-value of 0.00, indicating a high degree of statistical significance. The mean increase in satisfaction for the treatment group was 6.06, with a p-value of 0.00. The mean increase in satisfaction for the control group was 3.16, with a p-value of 0.00. The findings suggest that patient satisfaction levels in the treatment group surpassed those observed in the control group. The present study finds that education on discharge planning utilizing the Swanson Theory of Caring approach is associated with increased patient satisfaction in postoperative care.